The decision support facilitating the check-in service at the Chopin airport with the use of computational experiments in SIMIO - Kalbarczyk, Izabela; Kwasiborska, Anna; Gładyś, Sylwester (Transport, 2023)
Airlines strive to minimize the waiting time for passenger service at the airport. Modification of the passenger service process at check-in stands can be carried out by modelling and then simulating various scenarios in order to obtain time benefits. The organization of service for departing passengers is the most complex system, which includes numerous maintenance activities aimed at preparing them and their luggage for transport by aircraft. Therefore, this article aims to present a few scenarios to improve the passenger service process. Based on the research, assumptions were made for each check-in scenario. Then, the models were implemented in the SIMIO simulation program. In the next step, the passenger distribution for individual desks was modified and a comparison was made with the level of passenger service defined by International Air Transport Association (IATA). The simulation results for individual scenarios are presented and the benefits to be achieved after introducing the proposed changes are indicated. The simulations carried out showed 2 important elements in the current and proposed layout of the ticket and luggage service stations and the introduction of changes to the baggage desks. Article presents the specification of the time spent in the system and waiting in the queue. The conducted analyses have shown that the proposed concept will allow for taking over 40% of passengers using the adjacent Fast Bag Drop (FBD) stands. Research has shown that adding more machines for use will fully cover the demand for FBD. The conclusions presented in the article are valuable when introducing modernization of the passenger and baggage handling process. For future researches, it would be beneficial to test other simulation tools and other scenarios to compare these results with those presented in this article.